Novel laser induced photoacoustic spectroscopy for instantaneous trace detection of explosive materials. (August 2017) - El-Sharkawy, Yasser H.; Elbasuney, Sherif
Highlights: Instant detection of trace explosive materials. Standoff detection using novel LPAS technique. Customized optical sensor with superior performance. Validation of the developed customized optical sensor. Abstract: Laser photoacoustic spectroscopy (LPAS) is an attractive technology in terms of simplicity, ruggedness, and overall sensitivity; it detects the time dependent heat generated (thermo-elastic effect) in the target via interaction with pulsed optical radiation. This study reports on novel LPAS technique that offers instant and standoff detection capabilities of trace explosives. Over the current study, light is generated using pulsed Q-switched Nd:YAG laser; the generated photoacoustic response in stimulated explosive material offers signature values that depend on the optical, thermal, and acoustical properties. The generated acoustic waves were captured using piezoelectric transducer as well as novel customized optical sensor with remotely laser interferometer probe. A digital signal processing algorithm was employed to identify explosive material signatures via calculation of characteristic optical properties (absorption coefficient), sound velocity, and frequency response of the generated photoacoustic signal. Customized LPAS technique was employed for instantaneous trace detection of three main different high explosive materials including TNT, RDX, and HMX. The main outcome of this study is that the novel customized optical sensor signals were validated with traditional piezoelectric transducer. Furthermore, the customized optical sensor offered standoff detection capabilities (10 cm), fast response, high sensitivity, and enhanced signal to noise ratio. This manuscript shaded the light on the instant detection of trace explosive materials from significant standoffs using novel customized LPAS technique.